Suicide Note Sentiment Classification: A Supervised Approach Augmented by Web Data - Xu, Yan; Wang, Yue; Liu, Jiahua; Tu, Zhuowen; Sun, Jian-Tao; Tsujii, Junichi; Chang, Eric (Biomedical Informatics Insights, 2012)
Objective: To create a sentiment classification system for the Fifth i2b2/VA Challenge Track 2, which can identify thirteen subjective categories and two objective categories. Design: We developed a hybrid system using Support Vector Machine (SVM) classifiers with augmented training data from the Internet. Our system consists of three types of classification-based systems: the first system uses spanning n-gram features for subjective categories, the second one uses bag-of-n-gram features for objective categories, and the third one uses pattern matching for infrequent or subtle emotion categories. The spanning n-gram features are selected by a feature selection algorithm that leverages emotional corpus from weblogs. Special normalization of objective sentences is generalized with shallow parsing and external web knowledge. We utilize three sources of web data: the weblog of LiveJournal which helps to improve the feature selection, the eBay List which assists in special normalization of information and instructions categories, and the suicide project web which provides unlabeled data with similar properties as suicide notes. Measurements: The performance is evaluated by the overall micro-averaged precision, recall and F-measure. Result: Our system achieved an overall micro-averaged F-measure of 0.59. Happinesspeacefulness had the highest F-measure of 0.81. We were ranked as the second best out of 26 competing teams. Conclusion: Our results indicated that classifying fine-grained sentiments at sentence level is a non-trivial task. It is effective to divide categories into different groups according to their semantic properties. In addition, our system performance benefits from external knowledge extracted from publically available web data of other purposes; performance can be further enhanced when more training data is available.